Close call - Kipness, Elise Hart (Kipness, Elise Hart. Kate Green, 2025)
"With a hard-won Emmy now gracing her mantel, sports reporter and former Olympian Kate Green turns her energy to the action unfolding in Flushing Meadows. Working on a feature for her weekly TV show, she spotlights two of today's biggest female tennis stars: the sunny up-and-comer and the brash veteran. But the project goes sideways when one turns up missing. Following an interview with Kate, one player receives a sinister text with a disturbing photo of the other woman, bound and gagged. Kate calls on her estranged father, an NYPD detective, for help in launching a search. Although wary he's hiding something, she's not sure where else to turn. Their investigation leads to the victim's hometown - and a growing list of suspects. The kidnapper threatens to spill secrets that could destroy lives. Tangled up in a deadly web of deceit, Kate races to connect the dots and find the missing player ... before it's too late."--Publisher.